Simultaneous Estimation of Amlodipine Besylate and Benazepril Hydrochloride Using Derivative Spectroscopy - SAHAYA SAXENA, CHETAN; CHTURVEDI, S.C. (Asian Journal of Chemistry, 2010)
An accurate, sensitive and economical procedure for simultaneous estimation of amlodipine besylate and benazepril hydrochloride in tablet form has been developed. The method employed derivative spectroscopy, used first derivative spectra for the simultaneous estimation of amlodipine besylate and benazepril hydrochloride. The method is based on the measurement of the amplitude of the zero and first derivative spectra at 361 and 237 nm, respectively. Both drugs obey Beer's law in the concentration ranges employed for the analysis. The results of analysis have been validated statistically and by recovery studies.